FORMATION OF ALFALFA SEED PRODUCTIVITY DEPENDING ON VARIETAL CHARACTERISTICS - Марініч, Любов; Кочур, Олександр (SWorldJournal, 2025)
Abstract. elevance. Among the various leguminous herbs, alfalfa occupies a leading position. It contains 18-20% crude protein in dry matter, of very high quality. All essential amino acids necessary for the animal's organism are present in the forage, gre